Advantages and disadvantages of using the website cambridge one for the development of the writing skills of tenth graders - Torres Quezada, Andrés Sebastián (2024)
Foreign language e-learning is becoming more and more important because of the growing interest in this technology. Due to its availability, simplicity and ease of use, it has become a very popular method that helps improve the scope and quality of teaching English in educational institutions. Cambridge One which is a very efficient tool when performing didactic activities concerning learning a foreign language according to the level that students have for teaching to be effective and accurate. The research objectives are related to the impact of the Cambridge One platform on students and how learning developed using these digital tools; the methodology section outlines the research design and the methods used to collect and analyze data, the qualitative methodology has its own set of procedures, tools, and techniques that are selected based on the research questions, objectives, and the nature of the study. The results attempt to reflect the current trends in foreign language learning using technology and indicated many advantages to using digital platforms; using various IT tools, users can not only interact online, but also access the learning materials shared there and carry out various activities. on the other hand, the disadvantage is the lack of internet connection. To conclude, the research can take as a reference that allows the application of digital platforms in the educational field that can be related to information and communication technologies that can use to benefit the teaching of a second language.